(untitled) (Innovaciones Educativas, 2020)
During the pandemic caused by the virus named COVID-19, the educational system experienced a dramatic change from face-to-face to remote learning through the use of technological resources and various platforms to continue with the educational process. This event showed that the pedagogical models that were being implemented did not address the educational needs related to the progress and digital transformation throughout the health crisis. Therefore, this essay aims to reflect on the challenges and opportunities for improvement professors faced due to the pandemic. In fact, this interpretative essay discusses three educational challenges: (1) the contextual change, meaning, the migration from the classrooms to digital platforms and its impact in terms of the communication between instructors and students. (2) The accelerated learning process in the technological field represented a second challenge for the teaching staff as they developed technological abilities, in general terms, for the pedagogical mediation; process which was not frequently done previous to the pandemic. (3) The selection of effective technological tools that were free-access and user-friendly for fostering meaningful learning. This essay concludes with reflective thoughts that reassure teaching practices and the challenges faced during the pandemic as well as opportunities for improvement in relationship with the adaptation, changes, and modernization processes throughout an uncertain and continuously-changing period of time.